1972
DOI: 10.1084/jem.135.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Granulation Tissue as a Contractile Organ

Abstract: Contracting granulation tissues contain fibroblasts that develop characteristics typical of smooth muscle: (a) They contain an extensive cytoplasmic fibrillar system. (b) They show immunofluorescent labeling of their cytoplasm with human anti-smooth muscle serum. (c) The nuclei show complicated folds and indentations, indicative of cellular contraction. (d) There are cell-to-cell and cell-to-stroma attachments. (e) It is possible to extract similar quantities of actomyosin (having the same adenosine triphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
243
0
9

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 733 publications
(260 citation statements)
references
References 22 publications
8
243
0
9
Order By: Relevance
“…Ocorre, concomitantemente, reorganização da matriz extracelular, que se transforma de provisória em definitiva, cuja intensidade fenotípica, observada nas cicatrizes, reflete a intensidade dos fenômenos que ocorreram, bem como o grau de equilíbrio ou desequilíbrio entre eles. 32 Com o decorrer do processo de maturação e remodelagem, a maioria dos vasos, fibroblastos e célu-las inflamatórias desaparece do local da ferida mediante processos de emigração, apoptose ou outros mecanismos desconhecidos de morte celular. Esse fato leva à formação de cicatriz com reduzido número de células.…”
Section: -Fase De Remodelagemunclassified
“…Ocorre, concomitantemente, reorganização da matriz extracelular, que se transforma de provisória em definitiva, cuja intensidade fenotípica, observada nas cicatrizes, reflete a intensidade dos fenômenos que ocorreram, bem como o grau de equilíbrio ou desequilíbrio entre eles. 32 Com o decorrer do processo de maturação e remodelagem, a maioria dos vasos, fibroblastos e célu-las inflamatórias desaparece do local da ferida mediante processos de emigração, apoptose ou outros mecanismos desconhecidos de morte celular. Esse fato leva à formação de cicatriz com reduzido número de células.…”
Section: -Fase De Remodelagemunclassified
“…While investigating the mechanisms involved in wound contraction, it was found that granulation tissue fibroblasts progressively develop several features typical of smooth muscle cells (Gabbiani et al, 1972).…”
Section: Nemaline Myopathymentioning
confidence: 99%
“…6,7 The process is due to the action of the myofibroblast -a cell with fibroblast and smooth muscle characteristics distributed throughout granulation tissue present in wounds. 8 Contraction of myofibroblasts shrink the wound. This is followed by collagen deposition and cross-linking to maintain contraction.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is also known that contraction of the palmar fascia and surrounding structures in Dupuytren's contracture is directly related to the contractile properties of myofibroblasts. 8 In embryogenesis, failure of differentiation of the digits leads to scar tissue formation, which flexes the proximal inter-phalangeal joints with resulting camptodactyly. 5 Contractures can cause significant functional and/or cosmetic problems to patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation